2018
DOI: 10.3389/fmicb.2018.01852
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Concentrations of Copper, Alone or in Mixture With Arsenic, Can Impact River Sediment Microbial Community Structure and Functions

Abstract: In many aquatic ecosystems, sediments are an essential compartment, which supports high levels of specific and functional biodiversity thus contributing to ecological functioning. Sediments are exposed to inputs from ground or surface waters and from surrounding watershed that can lead to the accumulation of toxic and persistent contaminants potentially harmful for benthic sediment-living communities, including microbial assemblages. As benthic microbial communities play crucial roles in ecological processes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 71 publications
(73 reference statements)
1
31
0
Order By: Relevance
“…Based on the investigation of eight exoenzymes involved in various transformation steps (acid phosphatase, arylsulfatase, catalase, dehydrogenase, fluorescein diacetate hydrolase, protease, urease, and β-glucosidase), Chae et al [55] recommended β-glucosidase for the measurement of soil ecosystem health. The different temporal profiles of three enzymes (leucine aminopeptidase, phosphatase, and β-glucosidase) in the presence of metals during an incubation period of 21 days [56] and of four enzymes (acid phosphatase, arylsulfatase, fluorescein diacetate hydrolase, and urease) affected by fluorine [57] indicate that more than one enzyme is required for risk assessment applications.…”
Section: Exoenzyme Activity Testmentioning
confidence: 99%
“…Based on the investigation of eight exoenzymes involved in various transformation steps (acid phosphatase, arylsulfatase, catalase, dehydrogenase, fluorescein diacetate hydrolase, protease, urease, and β-glucosidase), Chae et al [55] recommended β-glucosidase for the measurement of soil ecosystem health. The different temporal profiles of three enzymes (leucine aminopeptidase, phosphatase, and β-glucosidase) in the presence of metals during an incubation period of 21 days [56] and of four enzymes (acid phosphatase, arylsulfatase, fluorescein diacetate hydrolase, and urease) affected by fluorine [57] indicate that more than one enzyme is required for risk assessment applications.…”
Section: Exoenzyme Activity Testmentioning
confidence: 99%
“…Nowadays, recent European restrictions on the use of chemicals and antibiotics for the management of bacterial diseases in agriculture have been enacted [ 14 ]. Copper-based treatments, despite being non-environmentally friendly and having a negative impact on microorganisms in soil, phyllosphere, and rhizosphere, are principally adopted to control bacterial plant diseases [ 15 , 16 ], while host resistance and appropriate agronomic practices, such as seeds certification, irrigation, and fertilization, are the principal strategies for integrated control of bacterial diseases in fields. During post-harvest, the more effective solutions to prevent bacterial diseases are proper storage conditions and good handling practices such as cleaning and disinfestations of equipment [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms are highly abundant in sediments, where they contribute to many ecological functions including the recycling of autochthonous and allochthonous organic matter (Schwarz et al, 2007), the production of greenhouse gas through anaerobic processes such as denitrification (de Klein et al, 2017) and methanogenesis (Billard et al, 2015), and the biodegradation of organic contaminants (Ghattas et al, 2017). Recently, Mahamoud Ahmed et al (2018) showed that environmental concentrations of Cu (i.e. about 40 mg kg−1 dw), alone or in a mixture with As at about the same concentration, can quickly impact the structure and a large set of functions of river benthic heterotrophic microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Research is needed to characterize the mechanisms that drive metal-induced tolerance and cotolerance in sediment microbial communities. Testing a 21-day realistic scenario for exposure to Cu (nominal concentration of 40 mg kg−1 dw, which is representaMve of high levels of Cu contaminaMon in French freshwater sediments (INERIS, 2010)), we recently showed in a laboratory channel experiment that natural river sediment microbial communities were structurally and functionally impaired by Cu (Mahamoud Ahmed et al, 2018). In the present study, we sought to expand these findings by characterizing changes in diversity, resistance and tolerance of sediment microbial communities subjected to chronic Cu exposure, and the resulting sensitivity to exposure to another metal.…”
Section: Introductionmentioning
confidence: 99%